Monitoring major city urban expansion in Kuala Lumpur and Penang City Centre - Yin, Izuandi; Mou, Leong Tan; Abang Mahmud, Dayang Shahrizat; S. Muthuveeran, Adam Aruldewan; Hassan, Mohd Azren; Yi, Lin Tew (Malaysian Institute of Planners, 2022)
Malaysia is currently undergoing heterogeneous land-use allocation and conversion in the city centre, resulting in leapfrog urban expansion to the suburban areas. Identification of the growth pattern from land-use conversion and urban growth has defined the limits of development, which could be a feasible way to alleviate the severity of these challenges. The research aims at the expansion factor for the built-up pattern of Kuala Lumpur (KL) and Penang City Centres. The objective of this research is to create a model on the new knowledge of urban built-up patterns generated from Landsat image data and comparison with built-up area from the change in land use, limitation of plot ratio, and floor space. The assessment of land-use changes is crucial in deciding the outcome for future development while considering the completion of committed development. This mechanism will help in the analysis of the data gathered using a remote sensing approach, which involves identifying the built-up area in KL City Centre using satellite images and examining the impact of land use patterns and varied plot ratios. In detail, the focus is directed towards a factor that influences the change of built-up area and development force. This will provide knowledge of Landsat images for the built-up area in urban expansion and the built-up limitations allocated by the local authority.